Digital Storytelling in Enhancing Student Behavioral and Cognitive Engagement in an EFL Classroom - Tira Rostia Wardini, - (2019)
Digital storytelling is considered as one of pedagogical tools that promotes student engagement in the classroom. This research is aimed to examine the process of creating digital storytelling in enhancing student behavioral and cognitive engagement in EFL classroom. To achieve the aim, this research employed qualitative case study with 36 students as the participants in tenth grade and the data gained from classroom observation, interview, and document analysis. The findings reveal that the students enhanced their behavioral and cognitive engagement throughout the process of creating digital storytelling project, namely introduction to example of digital storytelling project, brainstorming the ideas of digital story, drafting and making storyboard, and presenting digital story. Upon the process, the active behavioral engagement was demonstrated, where the students actively shared ideas, responded to teacher's question, participated in discussion, followed the instruction, and completed digital storytelling project. However, this research also found out that the students demonstrating the passive behavioral engagement. They appeared to have listened to the instruction, but not asking or responding to teacher's question and disinterested to the assignment. The student cognitive engagement was enhanced along the creation of digital storytelling process. It could be seen when the students actively used their prior knowledge and made the connection between their prior knowledge and the new information to create more structural knowledge and understand more complex knowledge in developing their digital story. This research has the implication to help the teacher engaged the students in the comfortable learning environment and promote 21st century learning.